Teachers' stand on the establishment of single-stream school - Ku Samsu, Ku Hasnita; Ab. Halim, Adlina; Lee, Yok Fee; Sulaiman, Mohd Hafiz (2012)
The issue of solidarity and nation-building cannot be separated. Thus, it obliges the government to improve the country's educational system by introducing the Vision School and the Student Integration Plan for Unity (RIMUP) policy. Unfortunately, there are still deficiencies in the system, as evidenced by the outcome and product of Vision Schools, which do not reflect the desired goal of unity. Thus, Single-stream Schools have become a hot topic of conversation among scholars and politicians as a promising alternate solution. It is recommended that the existing educational system return to embrace the spirit of the Razak Report 1956, whereby national integration is to be the key element of Malaysians. To what extent should the educational system be changed and manipulated to achieve integration? Is it true that Single-stream Schools are able to set the course for the path of unity? Thus, this writing aims to provide teachers' stand on Single-stream Schools in particular, besides identifying their stand on political parties' views on this issue. Hence, interviews were conducted with educators in Petaling Jaya and Gombak, who represented the mainstream education, and this included the Chinese and Tamil type schools. The interviews were based on research objectives, which intended to analyze their stand on Single-stream School.